À l’origine du roman graphique 40 hommes et 12 fusils. 2ᵉ&#8239partie&#8239: musées, monuments, lieux de mémoire et travail de documentation sur la toile - Marcelino Trương (Continents manuscrits)
The article presents the research work (family archives, living testimonies, trips to Vietnam, books, articles and videos) which preceded and accompanied the making-of of Marcelino Truong’s new graphic novel: 40 hommes et 12 fusils. Indochine 1954, published by Denoël Graphic, Paris, in October 2022. The genesis of an historical graphic novel indeed implies in-depth documentary research, for the author endeavours to achieve a rendering of the end of the Indochina war as observed from the Việt Minh side. Truong therefore studied in detail the political and military contexts of the period, without neglecting any of their visual aspects, such as scenery, costumes, equipment, as well as the emblematic objects reflecting the period. The author also scrutinised posters, leaflets, drawings and paintings of Việt Minh propaganda, and analysed the testimonies of war-artists, who contributed in their own way to the war effort initiated by President Ho Chi Minh. Truong brings to light a little-known aspect of this conflict by revealing the extent of the political and military assistance provided by Maoist China to the Vietnamese communist movement.The author also highlights the totalitarian nature of Vietnamese war communism, a draconian regime run by a State forged by war, which will maintain its grip on the population long after having achieved a hard-earned victory.